The serpent's egg - Wilhelm, Rolf Alexander 1927-2013 (MGM Home Entertainment, 2004)
An American trapeze act comes to pre-World War II Germany and two of the members are trapped inside Berlin after the other commits suicide. They find work with Dr. Vergerus at St. Ana's clinic, and soon discover that all is not what it appears to be